Phytoconstituents and Biological Activities of Zanthoxylum armatum Fruit Extract - Pathak, Ishwor; Rokaha, Shusma; Bajracharya, Kiran Bahadur (Journal of Nepal Chemical Society, 2021)
The essential oil and methanol extract of the fruit of Zanthoxylum armatum DC were extracted by hydro-distillation in the Clevenger apparatus and cold percolation technique respectively and their chemical and biological studies were performed. The chemical compositions of essential oil were analyzed by GC-MS analysis. The most abundant ingredient was Linalool (75.31%) followed by E-methyl cinnamate (11.73%) and limonene (9.45%). The nature of the functional groups present in the extract was analyzed by performing FTIR analysis. The methanol extract showed the presence of alkaloids, flavonoids, glycosides, polyphenols, terpenoids, volatile oils, tannins, and saponins. Biological activities of the oil and extract were evaluated by performing brine shrimp bioassay, antibacterial activity test, and antifungal activity test. Essential oil (LC50 = 76.70 µg/mL) and methanol extract (LC50 = 62.25 µg/mL) were found highly cytotoxic against brine-shrimp nauplii. The essential oil showed potent antibacterial activity against gram-positive bacteria Bacillus subtilis, Micrococcus leutus, and Staphylococcus aureus with the zone of inhibitions 11 mm, 16 mm, and 17 mm respectively and moderate antibacterial activity against the gram-negative bacteria Klebsiella pneumonia, Enterobacter cloacae, and Pseudomonas aeruginosa with the zone of inhibitions 9 mm, 5 mm and 6 mm respectively. The methanol extract was found to be effective against gram-positive bacteria only. Both oil and extract showed moderate antifungal activity against bacterial strains.